Implementation measurement in global mental health: Results from a modified Delphi panel and investigator survey - Christopher G. Kemp; Kristen Danforth; Luke Aldridge; Laura K. Murray; Emily E. Haroz (Cambridge Prisms: Global Mental Health, 2023)
Limited guidance exists to support investigators in the choice, adaptation, validation and use of implementation measures for global mental health implementation research. Our objectives were to develop consensus on best practices for implementation measurement and identify strengths and opportunities in current practice. We convened seven expert panelists. Participants rated approaches to measure adaptation and validation according to appropriateness and feasibility. Follow-up interviews were conducted and a group discussion was held. We then surveyed investigators who have used quantitative implementation measures in global mental health implementation research. Participants described their use of implementation measures, including approaches to adaptation and validation, alongside challenges and opportunities. Panelists agreed that investigators could rely on evidence of a measure’s validity, reliability and dimensionality from similar contexts. Panelists did not reach consensus on whether to establish the pragmatic qualities of measures in novel settings. Survey respondents (n = 28) most commonly reported using the Consolidated Framework for Implementation Research Inner Setting Measures (n = 9) and the Program Assessment Sustainability Tool (n = 5). All reported adapting measures to their settings; only two reported validating their measures. These results will support guidance for implementation measurement in support of mental health services in diverse global settings.